2022
DOI: 10.1039/d1cc06834b
|View full text |Cite
|
Sign up to set email alerts
|

New insight to superoxide radical-mediated degradation of pentachlorophenate: Kinetic determination and theoretical calculations

Abstract: This study reported the reactivity and mechanisms of superoxide radical (O2•-)-mediated transformation of pentachlorophenol. Our results indicated that O2•- alone exhibits limited effects on its degradation, and bimolecular nucleophilic substitution...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As such, both BMO-001-3A and BMO-001-3A-HNO 3 , modified with abundant surface-bridging hydroxyls, presented weaker electronegativity than BMO-001 and BMO-001-3A-KF. It is noticeable that NaPCP will dissociate into a negatively charged PCP – anion in water and engender an intensely repulsive force toward the negative interface . This repulsive force is not conducive to the NaPCP adsorption on BMO-001 with fairly strong electronegativity (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, both BMO-001-3A and BMO-001-3A-HNO 3 , modified with abundant surface-bridging hydroxyls, presented weaker electronegativity than BMO-001 and BMO-001-3A-KF. It is noticeable that NaPCP will dissociate into a negatively charged PCP – anion in water and engender an intensely repulsive force toward the negative interface . This repulsive force is not conducive to the NaPCP adsorption on BMO-001 with fairly strong electronegativity (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…It is noticeable that NaPCP will dissociate into a negatively charged PCP − anion in water and engender an intensely repulsive force toward the negative interface. 40 This repulsive force is not conducive to the NaPCP adsorption on BMO-001 with fairly strong electronegativity (Figure 2c). But the as-introduced surface hydroxyls of BMO-001-3A notably weakened its negative charge on the surface and thus effectively reduced the repulsion of NaPCP adsorption on the interface (Figure 2d).…”
Section: Bridging Hydroxyl-mediated Napcp Adsorptionmentioning
confidence: 98%
“…•− through measurements of second-order reaction rate constants. 18,19 Moreover, there have been studies questioning the important role of O 2…”
Section: Superoxide (Omentioning
confidence: 99%
“…Common quenchers of O 2 •– react more rapidly with hydroxyl radicals ( • OH) or hydrated electrons (e aq – ) (refer to Table S1). Some studies have also indicated the limited pollutant degradation capacity of O 2 •– through measurements of second-order reaction rate constants. , Moreover, there have been studies questioning the important role of O 2 •– in advanced oxidation processes such as catalytic ozonation and persulfate-based systems. , Therefore, it is necessary to reexamine the involvement of O 2 •– in pollutant reduction processes.…”
Section: Introductionmentioning
confidence: 99%
“…Only limited research has confirmed the contribution of O 2 •– for the direct degradation of contaminants . This could be attributed to relatively low reactivity of O 2 •– with organic contaminants. , Other studies showed that O 2 •– serves as a precursor to other reactive species such as • OH. , The nonradical oxidation pathway involves reactive species such as singlet oxygen 1 O 2 , high-valent metals, and surface-activated PS (or surface-active PS complex). Note that there are two low-lying-state oxygen species, 1 Δ g O 2 and 1 Σ g + O 2 .…”
Section: Ps Activation Approachesmentioning
confidence: 99%